Dispersal of vertebrates from between the Americas, Antarctica, and Australia in the Late Cretaceous and Early Cenozoic - Goin, Francisco Javier; Woodburne, Michael O.; Zimicz, Ana Natalia; Martin, Gabriel Mario; Chornogubsky Clerici, Laura
The early Paleocene diversity of metatherians in Tiupampan faunas of South America and the pre-Tiupampan Paleocene polydolopimorphian Cocatherium speak in favor of an earliest Paleocene or Late Cretaceous dispersal of metatherians from North America. No Late Cretaceous metatherian or eutherian mammals have been recovered to date in South America, but the late Campanian to Maastrichtian hadrosaurine dinosaurs in Argentina, as well as the late Maastrichtian of the Antarctic Peninsula, is evidence of a biotic connection to North America. Placental ?condylarths? in the Tiupampan may have been related to, and dispersedsouthward relative to, Puercan taxa in North America and perhaps reflect asomewhat later event in comparison to metatherians. Other than hadrosaurinedinosaurs, Late Cretaceous vertebrates of South America are basically Gondwananin affinities and reflect (and survived) the pre-106 Ma connection between SouthAmerica, Africa, and Antarctica. The potential for a Late Cretaceous dispersal of metatherians would be compatible with a continued dispersal to Australia at that time, also supported by plate tectonic relationships, notwithstanding the basically endemic coeval Australian dinosaur fauna, and recognizing the essential absence of a Late Maastrichtian land vertebrate record there. An early Paleocene connection between at least Antarctica and South America is documented by the presence of a monotreme in the Peligran fauna of Patagonia. This, coupled with the fact that post-Peligran mammal faunas in South America and the Antarctic Peninsula (from at least 52 Ma in that location) are composed of derived metatherian as well as placental mammals, suggests that dispersal of metatherians to Australia had been achieved prior to the Eocene. Such timing is compatible with the still plesiomorphic level of Australian metatherians from the early Eocene Tingamarra fauna of Australia, the marine sundering of the Tasman Gate at about 50 Ma and the development of a continuously marine southern coastline of Australia from ...